(3YbO GdLeGf aj JGQjN Cgd GdReGfs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s
(3ChdgG (B:s
(3jHJOF ef SfI (B727(3g` s
(3BNQgG (B:s
(3jfJgi ai SfI (B835(3g` s
(3GdehLhO efg eLdO jHJOF ef SfI (B727 (3hjfJgi ai SfI (B835s
(3QGLY HbjI fSN YPG GdcJGH HGdbSe GdChd ef GdagQSJ HQbe (B334s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B107 s
Keywords: (3GdJGQjNs